2018
DOI: 10.1016/j.ijid.2017.12.018
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of chronic comorbidities in chikungunya: A systematic review and meta-analysis

Abstract: Hypertension, diabetes and cardiac diseases may contribute to the severe outcome of CHIKV. Diabetic subjects may be at higher risk of severe infection. These findings may be relevant in developing public health measures and practices targeting CHIKV patients with comorbidities to avert the severe outcome of the infectious disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 49 publications
3
38
0
4
Order By: Relevance
“…Comorbidities such as hypertension, diabetes (both type I and type II) and cardiac disease can contribute to chikungunya severity and admissions to the ICU 60 . For example, diabetes can increase the severity and duration of chikungunya and in patients with diabetes and hyperglycaemia, chikungunya infection is associated with worsening of diabetic symptoms (such as poor glycaemic control and acute complications) 61 .…”
Section: Comorbidities and Co-infections Comorbiditiesmentioning
confidence: 99%
“…Comorbidities such as hypertension, diabetes (both type I and type II) and cardiac disease can contribute to chikungunya severity and admissions to the ICU 60 . For example, diabetes can increase the severity and duration of chikungunya and in patients with diabetes and hyperglycaemia, chikungunya infection is associated with worsening of diabetic symptoms (such as poor glycaemic control and acute complications) 61 .…”
Section: Comorbidities and Co-infections Comorbiditiesmentioning
confidence: 99%
“…Meanwhile, studies in other countries have shown that the rate of chronic cases is approximately 50% 5,9,10 . Deaths can occur in any of these phases, by direct or indirect action of the virus 11,12 . The age groups who are at higher risk of severe diseases include neonates who acquire the disease in the perinatal period, elderly 13 individuals, and those with pre-existing diseases 14 .…”
mentioning
confidence: 99%
“…A recent systematic review and meta-analysis found the following as the most prevalent comorbidities associated with CHIKV infection: hypertension (31.3%), diabetes (20.5%), heart diseases (14.8%), and asthma (7.9%), and this prevalence increased with age. 22 It is described that patients with CHIKV infection who are older have cardiovascular, neurologic, and respiratory disorders or with diabetes tend to present complications. 2 A recent study in our region found association between increasing number of deaths attributed to type 2 diabetes mellitus and CHIKV infection in Brazil in the same period, and this could be explained by the fact that the presence of comorbidities increases the severity of the infection.…”
Section: Discussionmentioning
confidence: 99%
“…23 Diabetes was also associated with chikungunya severity in another study. 22 Previous studies show that CHIKV cause osteoarticular disturbances, which are very frequent. Cardiovascular disease is also considered common, and infrequent manifestations of CHIKV infection include neurologic complications, skin lesions, kidney involvement, and gastrointestinal, hepatic, and hematologic disturbances.…”
Section: Discussionmentioning
confidence: 99%